How do Climate Shocks Affect the Impact of FDI, ODA and Remittances on Economic Growth? - Drabo, Alassane (Washington, D.C. : International Monetary Fund, 2021)
The three main financial inflows to developing countries have largely increased during the last two decades, despite the large debate in the literature regarding their effects on economic growth which is not yet clear-cut. An emerging literature investigates the dependence of their effects on some country characteristics such as human and physical capital constraint, macroeconomic policy and institutional capacity. This paper extends the literature by arguing that climate shocks may undermine the effect of Foreign Direct Investment (FDI), official development assistance (ODA) and migrants' remittances on economic expansion. Based on neoclassical growth framework, the theoretical model indicates that FDI, ODA, and remittances improve economic growth, and the size of the effect increases with good absorptive capacity. However, climate shocks reduce this positive effect of financial flows in developing countries. Using a sample of low and middle-income countries from 1995 to 2018, the empirical investigation confirms the theoretical conclusions. Developing countries should build strong resilience to climate change. Actions are also needed at global level to reduce greenhouse gases emissions, and build strong structural resilience to climate shocks especially in developing countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Climate; Economic Growth and Aggregate Productivity; Environmental Economics; International Finance; Macroeconomic Aspects of International Trade and Finance